Current Status of In Vitro Oocyte Growth and Development in Mammals - Yuji Hirao (Reproductive Medicine and Biology)
ABSTRACT Background In vitro‐matured oocytes play an increasingly vital role in livestock production and fertility treatments. However, oocytes grown in vitro are not yet practical for widespread use. So far, only mouse oocytes have achieved full developmental competence granted in vitro from the early growth stage. Methods This review provides an overview of established culture methods and conditions, analyzing their effects. When evaluating studies, outcomes specifically related to in vitro‐grown (IVG) oocytes rather than the follicle were prioritized. Main Findings Neonatal mouse first‐wave oocytes show a hypothesized linear volume increase, and IVG mouse oocytes have followed a similar developmental timeline across multiple studies. In other species, a proportion of bovine oocytes from early antral follicles achieved full size during 2‐week cultures, with some producing viable offspring, confirming developmental competence. Preantral follicle culture systems are typically designed to address specific research parameters, such as developmental competence assessment. Preimplantation embryogenesis has been reported in several species, including humans. Conclusion For species with oocytes ≥ 125 μm in diameter, normal growth can be achieved during the final 2 weeks of growth as shown in bovines. However, developing culture systems that can maintain follicle viability for the preceding 4–5 weeks remains a critical challenge.